A combination of split jumps and short sprints to increase the volleyball athletes’ leg muscle power and agility - I Ketut Yoda; Ketut Chandra Adinata Kusuma; I Gede Suwiwa; Hendriketa da Silva (Jurnal Keolahragaan, 2023)
pplying the right training methods can lead to optimal athlete performance. The use of one training method is common, and the use of a combination of two training methods is something new in training. The purpose of this study was to reveal the effectiveness of the combination of split jump training as a plyometric exercise with short sprint training on the leg muscle power capacity and agility of volleyball players. The research method in this research is a quasi experiment involving 40 samples (age: 20.85 ± 0.89 years, height: 178.69 ± 6.51 cm, and weight: 72.47 ± 8.02 kg). This study used a modified randomized pre-test and post-test design without a control group. The population of this study were volleyball players at Universitas Pendidikan Ganesha (Undiksha). Purposive sampling was chosen to determine the sample, namely 40 male student players.The sample was given training combining split jumps with short sprints for 4 weeks with details of 12 training sessions (3 times a week). The Jumpa DF and agility t-test were chosen as instruments to measure leg muscle power and agility. The collected data was analyzed using a paired t-test with a significance level of 5%. Before testing the hypothesis, start by testing the normality of the data using the Kolmogorov-Smirnova test and the homogeneity of the data using Levene’s with the help of SPSS 16.0. The results achieved show that there is a significant influence on the leg muscle power (sig 0.05) and agility (sig 0.05) of volleyball players. Based on the results of this data analysis, it can be concluded that the combination of split jump and short sprint training for 4 weeks has a significant effect on the results of leg muscle power and agility in male volleyball players. Seeing the findings above, it is hoped that volleyball coaches can apply this training method, specifically in the pre-competition phase, which requires a short time to improve leg muscle strength and agility at the same time.